(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Acute lymphoblastic leukemia (ALL) is the most common cancer seen in children worldwide and is the most common cancer in children under 14 years of age. Although there have been major advances in treatment approaches for childhood ALL, serious toxicities such as profound leukopenia frequently affect treatment and lead to life threatening consequences such as severe infections and even death. There has been a lot of interest in inter-individual differences in drug metabolizing enzymes in order to better adjust drug dosage and therapy. In this regards, Thiopurine S-Methyltransferase (TMPT) was the first pharmacogene that showed a substantial association with Mercaptopurine (6-MP) maximum tolerated dose and 6-MP related toxicities leading to the implementation of TPMT genotyping before drug administration Aim: To identify the most common TPMT polymorphism (TPMT*3A, TPMT*3B and TPMT*3C) and its frequencies in a sample of Iraqi ALL paediatric patients. Methods: A cross sectional study was performed for 79 patients with Acute lymphoblastic leukemia . Genotyping for (*3A , *3B , *3C ) the TPMT gene was performed by the allele-specific multiplex-PCR analysis method. Results: The TPMT*3A mutant allele was found in 18 patients with allele frequency of (22.8 %), while TPMT*3C mutant allele was detected in 5 children with allele frequency of 6.3% . But TPMT*3B mutant allele was not detected in whole sample ALL patients .The correlation between gender and the polymorphism was not statically significant as p-value 0.23.. Conclusion: TMPT genotyping is an essential tool to reduce the cytotoxic effects of the anticancer drug 6-MP in Iraqi paediatric patients with ALL .